OP0234 Infliximab therapy in patients with takayasu arteritis. (12th June 2018) - Park, E.H.; Lee, E.Y.; Lee, Y.J.; Ha, Y.J.; Choi, B.Y.; Yoo, W.-H.; Paeng, J.C.; Suh, H.Y.; Park, J.S.; Shon, S.; Song, Y.W.
Abstract : Background: Takayasu arteritis (TAK) is a chronic inflammatory disease that predominantly affects the aorta and its main branches. Glucocorticoids (GCs) are the cornerstones of the initial treatment of TAK. However, most patients relapse with steroid withdrawal. Objectives: To evaluate the efficacy and safety of infliximab (IFX) in Korean patients with active TAK. Methods: Patients with active TAK were enrolled in a single-centre prospective open label trial. Active disease was defined according to the National Institutes of Health (NIH) criteria. Concomitant GCs were tapered to prednisone ≤10 mg/day or equivalent at 2 weeks prior to the initiation of IFX. Patients received intravenous infusions of IFX, at a starting dose of 5 mg/kg at weeks 0, 2, 6, and then every 8 weeks, up to week 46, and were followed up to week 54. At week 30, patients with partial remission received increased dose of IFX by 1.5 mg/kg, and patients who failed with IFX terminated the study. At week 38 and 46, patients with symptom of active disease or high serum level of erythrocyte sedimentation rate (ESR) or C-reactive protein (CRP), were instructed to increase the IFX dose by 1.5 mg/kg, up to 9.5 mg/kg, at each point. All the patients underwent Positron Emission Tomography-Computed Tomography (PET-CT) at baseline and week 30. The primary efficacy end point was the achievement of partial or complete remission at week 30. Results: Twelve patients with TAK were enrolled and treated with IFX; 1 patient with study violation was excluded from analysis. At week 30, 3 patients (27.3%) achieved complete remission and 6 patients (54.5%) achieved partial remission. Statistically significant improvements were seen at week 30 for all of major secondary measures, including change from baseline in Indian Takayasu Clinical Activity Score 2010 ITAS 2010 (median 11.0, interquartile range [IQR] 10.0–11.8; 6.0, IQR 5.0–9.0, p=0.004), ITAS.A (14.0, IQR 12.0–14.0; 7.0, IQR 6.0–10.5, p=0.003) and serum levels of ESR (56.0, IQR 44.0–82.5; 26.0, IQR 20.0–56.5, p=0.031) and CRP (1.3, IQR 0.7–2.6; 0.2, IQR 0.1–2.1, p=0.019). PET parameters were significantly reduced, including maximum standardised uptake value (3.50, IQR 3.10–3.84; 3.10, IQR 2.49–3.27, p=0.023), target-to-vein ratio (1.34, IQR 1.13–1.95; 1.31, IQR 1.05–1.45, p=0.032), and target-to-liver ratio (2.38, IQR 1.47–3.05; 1.92, 1.51–2.18, p=0.014) from baseline to week 30. Serum levels of pentraxin-3, soluble human leukocyte antigen-E (sHLA-E), interleukin-6 tended to decrease, while tumour necrosis factor-α level increased after IFX therapy. There were no serious adverse events (SAEs) or AEs necessitating discontinuation of IFX. Conclusions: Treatment with IFX may lead to remission or improvement with lower glucocorticoid requirement in TAK (clinicaltrials.gov NCT02457585 ). Disclosure of Interest: None declared